Integrating the Metaverse into Omnichannel Fashion Retail: Customer Journey - Crespo, Verónica; Sánchez-Amboage, Eva (Mercados y Negocios, 2025)
The objective of this paper is to investigate how fashion brands incorporate metaverse retailing into their omnichannel strategies. To this end, the metaverse is conceptualised as a retail channel, and a real case was analysed using content analysis to examine its omnichannel integration into a leading fashion brand. Finally, we explore the opportunities, challenges, and implications of integrating the metaverse into omnichannel retail and its impact on the consumer journey. Our study reveals that, despite initial branding coherence and partially integrated product information on the metaverse, at present, there is no genuine integration of these platforms within omnichannel retail strategies. Metaverse channel currently functions in isolation from established e-commerce touchpoints, yielding disjointed customer journeys.